Niepełnosprawność w oku patrzącego. Konstruktywistyczna filozofia niepełnosprawności i antypsychiatria = Disability in the eye of the beholder. Constructivist philosophy of disability and antipsychiatry - Grabizna, Adrianna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
We count the existence of philosophy in thousands of years, but the philosophy of disability only in few decades. Many of its voices are constructivist, discussing the ontological status of disability, opposing the naturalization and biologization of disability.
Keywords: filozofia niepełnosprawności; antypsychiatria; konstruktywizm; spór o uniwersalia; DSM; philosophy of disability; antypsychiatry; constructivism; quarrel of the universals